International Branch Campuses: Current Trends and Future Possibilities - Wilkins, Stephen (International Higher Education, 2024)
In recent years, for every international branch campus that closed, three or four new ones opened. The future success of such campuses will likely depend to a great extent upon the ability of institutions to attract students and funding, match accreditation requirements, and maintain favorable relationships with host country partners. Geopolitics and the desire of countries to host such campuses will also be of high importance.